Reactive Oxygen Species Bridge the Gap between Chronic Inflammation and Tumor Development. (28th June 2022) - Yu, Weihua; Tu, Yongmei; Long, Zi; Liu, Jiangzheng; Kong, Deqin; Peng, Jie; Wu, Hao; Zheng, Gang; Zhao, Jiuzhou; Chen, Yuhao; Liu, Rui; Li, Wenli; et al.
Abstract : According to numerous animal studies, adverse environmental stimuli, including physical, chemical, and biological factors, can cause low-grade chronic inflammation and subsequent tumor development. Human epidemiological evidence has confirmed the close relationship between chronic inflammation and tumorigenesis. However, the mechanisms driving the development of persistent inflammation toward tumorigenesis remain unclear. In this study, we assess the potential role of reactive oxygen species (ROS) and associated mechanisms in modulating inflammation-induced tumorigenesis. Recent reports have emphasized the cross-talk between oxidative stress and inflammation in many pathological processes. Exposure to carcinogenic environmental hazards may lead to oxidative damage, which further stimulates the infiltration of various types of inflammatory cells. In turn, increased cytokine and chemokine release from inflammatory cells promotes ROS production in chronic lesions, even in the absence of hazardous stimuli. Moreover, ROS not only cause DNA damage but also participate in cell proliferation, differentiation, and apoptosis by modulating several transcription factors and signaling pathways. We summarize how changes in the redox state can trigger the development of chronic inflammatory lesions into tumors. Generally, cancer cells require an appropriate inflammatory microenvironment to support their growth, spread, and metastasis, and ROS may provide the necessary catalyst for inflammation-driven cancer. In conclusion, ROS bridge the gap between chronic inflammation and tumor development; therefore, targeting ROS and inflammation represents a new avenue for the prevention and treatment of cancer.